# calculus (gr 12)

posted by .

Evaluate each of the following. Show all your calculations.
a) f'(3) if f(x)  = x^4 − 3x

b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8

c) f" (1) if f(X)  = −3x^2 − 5x + 7

d)f" (−3) if f(x)  = 4x^3 − 3x^2 + 2x − 6

e) f'(0) if f(x)  = 14x^2 + 3x − 6

f)f" (4) if f (x) = x^5 + x^4 − x^3

g)  f" (1/3) if f(x) = −2x^5 + 2x − 6

h) f′ (3/4)if f(x) = −3x^3 − 7x^2 + 4x − 11

• calculus (gr 12) -

pick one that gives you trouble, and I can walk you through it.

## Similar Questions

1. ### calculus

Find an equation for the surface consisting of all points P(x, y, z) equidistant from the point P(0, 1, 0) and the plane x = 3. Answer Choices: 1. y2 + z2 − 6x + 2y − 8 = 0 2. x2 + z2 + 6y − 2z − 8 = 0 3. y2 …
2. ### biology

Given the part of the molecule shown below, can the underlined atom participate in a hydrogen bond with an approriate bonding partner?

Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
4. ### calculus (gr 12)

Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
5. ### calculus (gr 12)

Evaluate each of the following. Show all your calculations. f′ (3/4)if f(x) = −3x^3 − 7x^2 + 4x − 11
6. ### calculus

Evaluate each of the following. Show all your calculations. f" (−3) if f(x)  = 4x^3 − 3x^2 + 2x − 6
7. ### calculus (gr 12)

Evaluate each of the following. Show all your calculations. f" (−3) if f(x)  = 4x^3 − 3x^2 + 2x − 6
8. ### calculus

Evaluate each of the following. Show all your calculations. f′ (3/4)if f(x) = −3x^3 − 7x^2 + 4x − 11
9. ### calculus

Evaluate each of the following. Show all your calculations. f" (−3) if f(x)  = 4x^3 − 3x^2 + 2x − 6